Sudden sensorineural hearing loss: a rare presentation of dengue fever - Mughal, Ainulakbar; Mohammad Wasif; Sayed Akbar Abbas; Ghaloo, Shayan Khalid; Vardag, Abdul Basit Shah; Awan, Muhammad Ozair (Journal of the Pakistan Medical Association, 2022)
Sudden Sensorineural Hearing Loss (SSNHL) is described as a hearing loss of at least 30db in three frequencies in pure tone audiogram over 3 days or less. The cause may be infectious, vascular, systemic immune-mediated or idiopathic. Multiple viral infections have been associated with SSNL. However, dengue fever, which is an RNA viral disease that is directly transmitted by a mosquito of genus Aedes, has been reported to present with SSNHL only thrice in existing literature to the best of our knowledge. There are multiple different proposed mechanisms of SSNHL in viral infections and multiple viruses have been proven to cause hearing loss. However, dengue virus is not one of them. In majority of cases of SSNHL, the exact cause is very difficult to determine. We report the case of a gentleman who had unilateral SSNHL after dengue fever. Keywords: Dengue; Hearing Loss; Virus